E-Government: evolution of the state - Кудрявцев, О. Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The dynamic development of information and communication technologies (ICTs) determines the process of implementing e-government for the effectiveness of communication at the level of „society-state”. Carried out the conceptualized definition of „electronic government" in the context of political science. Analyze of  the Singapore model of electronic government were made. The difficulty of implementing e-government in Ukraine were revealed.